INFORMATION SYSTEM DESIGN FOR MICRO CREDIT BANKS - Linda Wahyu Widianti (Majalah SIKOMTEK, 2010)
Developments in the banking system nder its wings for small businesses (market traders), which are many and are the backbone of the people on the Indonesian economy. To help the small entrepreneurs who are usually very shy in touch with the bank. Products of this micro service within its implementation constitute a computer-based information systems and management processes utilizing information technology as a tool for data processing.Â  Information system used for calculation of return on a loan and is available at this micro service are semi automatic because many feel That matter deficiencies. Disadvantages include the ineffectiveness of the time used in making the loan payment calculation reports of customers, it is disturbing performance in the billing clerk.Â  Micro-services information system design of the proposed implementation will be realized byusing a computer. This system can provide advantages such as speed up the preparation of reports and data storage more reliable, so it can provide accurate and reliable information that will ultimately produce an effective performance and efficient performance in supporting the decision making process for its users